The Journey of Marketing Research in Driving Successful Marketing Strategies - Putra, Gani Ahmad (Advances in Business & Industrial Marketing Research, 2024)
The study aims to explore the transformative impact of artificial intelligence (AI) and machine learning (ML) algorithms in marketing research, with a focus on understanding consumer behavior and optimizing marketing strategies. The research design and methodology involve a comprehensive review of recent literature and empirical studies in the field of marketing, analyzing trends, challenges, and opportunities associated with the integration of AI and ML technologies. The findings reveal that AI-driven analytics offer businesses unprecedented opportunities to gain deeper insights into consumer behavior, personalize marketing efforts, and optimize campaign performance. However, the widespread adoption of AI in marketing research also raises ethical considerations related to data privacy, transparency, and algorithmic bias. The implications of these findings underscore the importance of balancing the benefits of AI-driven insights with ethical practices to build consumer trust, maintain regulatory compliance, and foster long-term relationships with stakeholders.